2018
DOI: 10.1556/2006.7.2018.118
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related differences in cue-elicited cravings in Internet gaming disorder: The effects of deprivation

Abstract: BackgroundOnline gaming has become a popular leisure activity, in which males more frequently develop Internet gaming disorder (IGD) compared to females. However, gender-related neurocognitive differences have largely not been systematically investigated in IGD.MethodsCue-elicited-craving tasks were performed before game playing and immediately after deprivation operationalized as a forced break from gaming when the Internet was disconnected. Ninety-nine subjects with IGD (27 males and 22 females) or recreatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 80 publications
(102 reference statements)
5
39
0
8
Order By: Relevance
“…Being male was significantly associated with internet gaming disorder. Women may show better executive control than men when facing gaming cues, which may provide resiliency against developing IGD [16]. Another study identified the differences of the brain in men and women with IGD [17].…”
Section: Discussionmentioning
confidence: 99%
“…Being male was significantly associated with internet gaming disorder. Women may show better executive control than men when facing gaming cues, which may provide resiliency against developing IGD [16]. Another study identified the differences of the brain in men and women with IGD [17].…”
Section: Discussionmentioning
confidence: 99%
“…Second, most study subjects were male (only five females). As such, future studies should examine the extent to which the findings may apply to female populations, especially as gender-related differences have been observed in neural correlates in IGD populations Dong, Wang, Wang, et al, 2019;Dong, Zheng, et al, 2018). Third, although we performed a DCM analysis that suggests that executive control over lentiform activation may improve with recovery, we cannot exclude other possible explanations that should be investigated directly in future studies.…”
Section: Limitationsmentioning
confidence: 99%
“…Because older adults have been routinely excluded from MRI studies that do not focus on aging, and taking into account shared neurodegenerative impacts of addiction and biological aging (Cheng et al, 2013), there is relatively little known about FDCR in older adults (e.g., > 65-years). In terms of sex/gender, multiple studies have demonstrated sex-/gender-related differences in FDCR, particularly in participants who smoke cigarettes (Francis J. McClernon, Kozink, & Rose, 2008;Wetherill et al, 2013), individuals with cocaine dependence (Joseph et al, 2019;Potenza et al, 2012), and those with gambling (Kober et al, 2016) and gaming Dong, Wang, Wang, Du, & Potenza, 2019;Dong, Zheng, et al, 2018) disorders, which may depend, in part, on menstrual cycle phase in women (T. R. Franklin, Jagannathan, Ketcherside, Spilka, & Wetherill, 2019).…”
Section: Participant Characteristicsmentioning
confidence: 99%